Diagnostic accuracy of endostatin for malignant pleural effusion: A clinical study and meta-analysis. Issue 5 (3rd September 2015) - Tian, Panwen; Shen, Yongchun; Feng, Mei; Zhu, Jing; Song, Haili; Wan, Chun; Chen, Lei; Wen, Fuqiang
Abstract: Background . The diagnosis of malignant pleural effusion (MPE) remains a clinical challenge. Many studies suggest that endostatin is a potential marker for MPE. This study aimed to determine the diagnostic value of endostatin with respect to MPE and to summarize the overall diagnostic performance of endostatin via a meta-analysis. Methods . Pleural effusion samples from patients with both malignant and nonmalignant disease were collected, and the pleural levels of endostatin and carcino-embryonic antigen (CEA) were subsequently measured. The diagnostic performances of endostatin and CEA were analyzed via standard receiver operator characteristic curve analysis methods, using the AUC as a measure of accuracy. The overall diagnostic accuracy of endostatin for MPE was summarized through a bivariate meta-analysis with standard method recommended. Results . Fifty-two patients with MPEs and 64 patients with benign pleural effusions (BPEs) were included this study. Pleural endostatin levels were significantly increased in the setting of MPE compared with BPE (104.78 ± 64.58 vs 56.81 ± 28.84 ng/ml; p < 0.001). Using a cutoff value of 79.7 ng/ml, the sensitivity and specificity of endostatin in diagnosing MPE were shown to be 51.92% and 85.94%, respectively, and the AUC was 0.747. The combination of endostatin and CEA enhanced diagnostic performance with respect to MPE. In addition to this study, another eight studies were included in this meta-analysis. The pooled diagnostic estimates were 0.69 for sensitivity and 0.78 for specificity. The positive likelihood ratio and negative likelihood ratio for endostatin were 3.16 and 0.40, respectively. The diagnostic odds ratio was 7.89, and the AUC of the summary receiver operator characteristic curve was 0.79. Conclusion . Pleural levels of endostatin are increased in the setting of MPE. However, endostatin exhibits a limited efficacy for the diagnosis of MPE and shows a relatively low sensitivity. The assessment of endostatin in combination with CEA may enhance diagnostic accuracy with respect to MPE.